Synthesis of acrolein by gas-phase dehydration of glycerol over silica supported bronsted acidic ionic liquid catalysts - Munshi, Mudassir K.; Lomate, Samadhan T.; Deshpande, Raj Madhukar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein. RESULTS: Dehydration of glycerol to acrolein was performed over several silica supported Bronsted acidic ionic liquids as catalysts. All the catalysts prepared were active for the synthesis of acrolein (conversion of glycerol was observed in the range 35-90% with selectivity to acrolein in the range 29-58%). CONCLUSIONS: Catalyst prepared from triphenyl (3-sulfopropyl) phosphonium 4-methylbenzenesulfonate gave good activity and selectivity at 4 h reaction time. The conversion of glycerol decreased with increase in glycerol concentration. Higher temperature (325 degrees C) resulted in significantly lower conversion as well as selectivity to acrolein. With the use of two additional traps cooled to -7 degrees C, the selectivity to acrolein increased significantly for good catalysts. (C) 2010 Society of Chemical Industry
Keywords: acidic ionic liquids; acrolein; glycerol dehydration; supported catalyst

Synthesis of glycidol from glycerol and dimethyl carbonate using ionic liquid as a catalyst - Gade, Swapna M.; Munshi, Mudassir K.; Chherawalla, Batul M.; Rane, Vilas H.; Kelkar, Ashutosh A. (Catalysis Communications, 2012)
Transesterification of dimethyl carbonate with glycerol has been investigated using various ionic liquids as catalysts. Synthesis of glycidol with high selectivity (78%) has been achieved using tetramethylammonium hydroxide ([TMA][OH]) as a catalyst at 80 degrees C. Effect of various reaction conditions on the activity and selectivity was investigated and catalyst concentration had a significant influence on conversion as well as selectivity to glycidol. Activity as well as selectivity of the catalyst decreased significantly with increase in moisture content. Recycle experiment indicated slight drop in glycerol conversion and selectivity to glycidol because of dilution of reaction mixture and also the presence of products from the initial experiment. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Glycerol carbonate; Glycidol; Ionic liquid; Transesterification of glycerol

1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU): a highly efficient catalyst in glycerol carbonate synthesis - Munshi, Mudassir K.; Gade, Swapna M.; Mane, Manoj V.; Mishra, Deepti; Pal, Sourav; Vanka, Kumar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Molecular Catalysis A-Chemical, 2014)
Transesterification of dimethyl carbonate (DMC) with glycerol (GLY) was investigated using various amines as catalysts. Amidines like 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) were found to be the best catalysts for this reaction. Best results: 98% conversion of GLY with 96% selectivity to GC (TON: 9408), were obtained with DBU as a catalyst. Effect of various reaction conditions on activity and selectivity were investigated using DBU as catalyst. The mechanism of the reaction was investigated with the help of H-1, C-13 and N-15 NMR analysis and OFT calculations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DBU; Glycerol; Glycerol carbonate; transesterification

Efficient synthesis of glycerol carbonate/glycidol using 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) based ionic liquids as catalyst - Munshi, Mudassir K.; Biradar, Pradeep S.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol to glycerol carbonate has been catalyzed efficiently using basic ionic liquids as catalysts. Activity of all the ILs tested is very high and the best result (96% conversion with 82% selectivity to glycerol carbonate and 18% selectivity to glycidol) was obtained using IL1 as catalyst. The effect of catalyst loading has significant influence on the selectivity pattern. The higher activity of the ionic liquid is explained with a plausible mechanism based on the co-operative effect of both cation and anion.

Role of cation-anion cooperation in the selective synthesis of glycidol from glycerol using DABCO-DMC ionic liquid as catalyst - Munshi, Mudassir K.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol has been investigated using 1,4-diazabicyclo [2.2.2] octane (DABCO) based ionic liquid as a catalyst. DABCO reacted with dimethyl carbonate to form ionic liquid as the reaction progressed. Though the basicity of DABCO based ionic liquid was lower than that of DABCO, the catalytic activity and selectivity to glycidol was higher with DABCO based ionic liquid as a catalyst, indicating that basicity may not be the only criterion in deciding activity and selectivity of the reaction. The cooperative effect of the cation and anion of the ionic liquid is responsible for the observed results. The best results (97% glycerol conversion with 83% selectivity to glycidol and 17% selectivity to glycerol carbonate) were obtained using DABCO based ionic liquid as a catalyst. A plausible mechanism involving the role of both the cation and anion of the ionic liquid has been proposed.

Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.